The Impact of the Covid-19 Pandemic on Staple Food Prices in Medan - Manihuruk, Ekamonika; Rachmadhan, Aditya Arief (Universitas Galuh, 2024)
The Covid-19 pandemic has restricted public access and disrsupted food distribution. As one of the most affected cities, Medan is facing the threat of rising food prices due to the Covid-19 pandemic. This study aims to analyze the impact of the Covid-19 pandemic on staple food prices in Medan. The commodities that are the focus of the research are: (1) rice, (2) white sugar, (3) palm oil, (4) chicken eggs, (5) chicken meat, and (6) beef. This study used weekly time series data which is divided into two periods; the period before the Covid-19 pandemic (2018-2019) and during the Covid-19 pandemic (2020-2021). Data analysis was performed using the ANOVA method; where the price difference shows the impact of the Covid-19 pandemic on food prices. The results of the analysis show that the Covid-19 pandemic has had a significant impact on increasing staple food prices in Medan for the commodities: (1) rice, (2) white sugar, (3) palm oil, (4) chicken eggs, and (5) beef. The results of the study also show that the Covid-19 pandemic has had a negative impact on the food security in Medan.